EKSPLORASI HAMBATAN CALISTUNG PADA PESERTA DIDIK KELAS 1 DI SDN 5 JAMBANGAN - Arini Wardhalia; Devi Ayu Safitri; Nabila Diyaul Aulia; Venti Rahmawati; Ovi Mulyasari; Beti Istanti Suwandayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the barriers to reading, writing, and arithmetic skills among first-grade students at SDN 5 Jambangan and to identify the internal and external factors influencing these difficulties. Employing a qualitative case study approach, data were collected through classroom observations, in-depth interviews with teachers and parents, and document analysis of students’ learning outcomes. The findings reveal that difficulties in reading, writing, and arithmetic are caused by a combination of internal factors, including low phonological awareness, underdeveloped cognitive abilities, weak fine motor skills, and low learning motivation. In addition, external factors contributing to these challenges include limited academic guidance at home, insufficient learning media and facilities, family communication patterns, and unsupportive learning environments. Observation results indicate that 14.8% of students experience difficulties in reading and writing, while 7.4% encounter challenges in arithmetic skills. These difficulties are primarily associated with low phonological awareness and inadequate fine motor development. The findings highlight that barriers to reading, writing, and arithmetic are multidimensional in nature and require integrated interventions involving both schools and families. This study recommends the enhancement of phonics-based instructional methods, strengthened early literacy and numeracy stimulation, and more intensive collaboration between teachers and parents to support the holistic development of students’ foundational academic skills.